IWRM [Integrated Water Resources Management] in Uganda - progress after decades of implementation - Nicol, Alan; Odinga, W. (2016)
Uganda lies almost wholly within the Nile Basin and is a country characterised as well-endowed with water resources. Receiving considerable inflows of aid since the early 1990s, some of this aid emerging after the 1992 Earth Summit in Rio de Janeiro enabled the country to begin a process of Integrated Water Resources Management (IWRM), taking the lead from Chapter 18 of Agenda 21. With a focus on more comprehensively managing the country’s critical water endowment amidst growing pressure on the resource, bilateral technical assistance and financial support played a large part in backstopping these national efforts. Nevertheless, in spite of this support and government backing, some two decades later implementation on the ground remains thin and the exercise of IWRM in practice is limited. This paper examines the Ugandan IWRM experience and identifies complex political-economy issues lying at the heart of current challenges. It argues that rarely is there likely to be an easy fix to sustainable financing and suggests the need for stronger citizen engagement and buy-in to the wider logic of IWRM to support longer-term effectiveness and sustainability.